Power Generation from Waste Heat Using Heat Pipe and Thermoelectric Generator. (August 2015) - Remeli, M.F.; Kiatbodin, L.; Singh, B.; Verojporn, K.; Date, A.; Akbarzadeh, A.
Abstract: This paper presents the investigation of power generation using the combination of heat pipes and thermo-electric generators. A majority of thermal energy in the industry is dissipated as waste heat to the environment. This waste heat can be utilized further for power generation. The related problems of global warming and dwindling fossil fuel supplies has led to improving the efficiency of any industrial process being a priority. One method to improve the efficiency is to develop methods to utilize waste heat that is usually wasted. Two promising technologies that were found to be useful for this purpose were thermoelectric generators and heat pipes. Therefore, this project involved making a bench type, proof of concept model of power production by thermoelectric generators using heat pipes and simulated hot air. The laboratory experiment of the proposed system was obtained with a counter flow air duct heat exchanger. The results obtained show an increase in the ratio of mass flow rate in upper duct to lower duct has a positive effect on the overall system performance. A higher mass flow rate ratio results in a higher amount of heat transfer and higher power output. The proposed system can be used for waste heat recovery from the industry where thermal energy is used in their daily process.